(untitled) (LEARNing Landscapes, 2018)
In this interview, digital consultant and author Dean Shareski talks about the fundamental aspects of authentic learning: joy, wonder, play, and community. He believes that technology can bring a sense of fun and curiosity to the classroom by allowing students to do things they couldn’t do before, like editing photographs or meeting a scientist from another part of the world. School communities can now share their innovations with the community at large and also with schools in different countries. Teachers, he says, should see themselves as artists and not be afraid to play and explore new opportunities. As final advice to teachers and parents, he suggests that we let kids be kids and experience the joy of childhood.